A FORMULATION OF ORALLY DISINTEGRATING SECANG (CAESALPINIA SAPPAN L.) TABLETS AS AN ANTIOXIDANT WITH HYDROXYPROPYL CELLULOSE AS A MASKING AGENT - Mustarichie, Resmi; PRIAMBODO, DRADJAD (International Journal of Applied Pharmaceutics, 2019)
Objective: The objective of this research was to formulate Orally Disintegrating Tablets (ODT) preparations for secang (Caesalpinia sappan L.) wood extract as antioxidants that met the requirements as a pharmaceutical preparation. Methods: Three ODT formulas were made using the composition of the extract of secang wood, HPC-H, kollidon® CL, Avicel® PH 101, mannitol, acesulfame, magnesium stearate, citric acid, and menthol. The bitter taste of the extract of wood secang was covered with the Hydroxy Propyl Cellulose High Substitution (HPC-H) masking agent. Variations in HPC-H concentration were 4%, 4.5%, and 5%. The evaluation of tablet print mass tested included water content, flow velocity, and resting angle, real density, incompressible density, and compressibility. Evaluation of tablets tested included weight uniformity, uniformity of size, hardness, friability, and disintegration time. The tablet antioxidant activity testing was carried out by the Diphenylpicylhydrazyl (DPPH) method. Results: The results showed that all ODT formulas of secang wood extract were fulfilling the requirements as a tablet preparation according to Indonesian Pharmacopoeia IV. IC50 values ​​obtained from antioxidant testing on the three ODT formulas for a secang wood extract for formula I was 3.614 ppm, formula II was 3.464 ppm, formula III was 3.173 ppm, and the wood extract was 3.757 ppm. Conclusion: The results obtained in this research work clearly indicated ODT formulas of secang wood extract fulfilled Indonesian Pharmacopea IV requirement and belong to the category of very strong antioxidants because they have an IC50 value of less than 50 ppm.